What did they do with the children who went through kidnapping operations? Child victims: beyond appropriation (Argentina, 1977-1979) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2023)
This article aims to reconstruct and analyze various repressive practices perpetrated on more than a hundred boys and girls who experienced kidnapping operations during the last dictatorship regime in Argentina, children of detained-disappeared persons in the Atlético-Banco-Olimpo repressive circuit. (ABO, 1977-1979).From a qualitative strategy, we carry out this reconstruction and analysis based on what is narrated, both in judicial testimonies and in the context of meetings, by those who survived these various types of violence in their childhoods.This work is based on a fundamental purpose: to make visible child victims and the various forms of violence they suffered, repressive practices have not been fully analyzed from the legal field and recently addressed in the academic research; beyond the appropriation of children that has numerous and valuable studies.